History, Islam and Philosophy of History: A Critical Thinking in History as the Lesson of the Past (Al-Qamar, 2023)
Primarily this is an analytical study of the philosophy of history. Usually, the word history is used for the past events of man activities and as a discipline and subject, History is considered an important study about the past activities of the human being. History is considered as the record of the human past and the main objective of history writing was to find the causes about the occurrence of any event and investigated it with logical arguments. While Islam contributed lot for history and it is said that religion leads to history. Islam as religion provided the principles of truth justice and honesty to form before distance of history and the history leads humanity along the path of peace and progress. it is observed that it will be interesting to know what guidance we get from the Holy Quran history. we have found the fundamentals historical creative season in the Holy Quran and traced it the source of inspiration for the Muslim historian in their historiography. Philosophy of history is a branch of history which studied the human activities on the basis of causes as history is considered to be the study of causes. The term philosophy of history initially used by the great philosopher and historian Voltaire. The term philosophy of history means that the knowledge of history should be read and understood in a philosophical way instead of just reading it as a story. Philosophy of history was divided in two types as speculative and analytical philosophy of history. Due to the writings of various thinkers, the world was taking extraordinary interest in the reality and essence of time and place while recording the events. Thanks to Karl Marx and some famous European historians, the subject of the Philosophy of history was also given special importance in Europe. History is not only the name of the events, but the knowledge that interprets the social, political and cultural condition of the mentioned period with the events. Therefore, the usefulness of the philosophy of history in the knowledge of history is certain. Explained the events in the light of cultural reasons. This paper highlights the importance of the Philosophy of history as lesson of the past for the mankind.
Keywords: History; Truth; Philosophy of History; Voltaire; Renaissance; Europe; Islam